Ontogeny of actin and microsomal antigens in gastric parietal cells. - Ceredig, R (1978)
Six fetal and 10 neonatal rat or mouse stomachs and a 14-week human fetal stomach were examined for immunofluorescence reactivity with four sera containing parietal cell antibody (PCA) and four other sera containing smooth muscle antibody (SMA). In rat and mouse stomachs, parietal cells first reacted with PCA in 19-day fetal stomachs and with SMA in two-day neonatal rat stomachs or newly-born mouse stomachs. SMA reactivity with fetal rodent stomachs was restricted to the cytoplasm of smooth muscle, the apices of gastric mucosal cells, and the cytoplasm of fibroblasts surrounding invaginating gastric pits. In the 14-week human fetal stomach, parietal cells stained with PCA but not with SMA. Specificity of the staining reactions was established by the complete inhibition of PCA staining by serum absorption with a gastric microsomal fraction but not with actin. Conversely, the SMA staining was abolished by serum immunoabsorption with actin but not with microsomal fraction. These observations, indicating that the development of the parietal cell microsomal antigen precedes that of actin, may be used to distinguish between the staining of parietal cells by SMA and PCA.